Automated Hand Sanitizer Dispensing System Based on Arduino for Kanisius Ungaran Elementary School - Indra Ava Dianta; Dwi Setiawan; Thelsi Seubelan (STEKOM PRESS, 2023)
In the era of the new normal, maintaining health and hygiene has become critically important, especially in preventing the spread of viruses. One effective way to achieve this is through regular handwashing. Schools are particularly susceptible to the transmission of viruses and bacteria, which is why it's crucial to implement an effective hand sanitizer system. However, the use of conventional hand sanitizer bottles that require manual pressing or opening still carries the risk of virus transmission. Therefore, there is a need for the development of an automatic hand sanitizer system to reduce the risk of virus transmission. This research aims to design an Arduino-based automatic hand sanitizer system at SD Kanisius Genuk. The automatic hand sanitizer system utilizes an ultrasonic sensor to detect the distance between an object, in this case, a hand, and the hand sanitizer. When the hand approaches within a certain distance, the hand sanitizer fluid is dispensed automatically through a mini 5V pump. Additionally, the device features a liquid level sensor that provides information about the hand sanitizer fluid level via an LCD screen. The theoretical significance of this research lies in enriching knowledge about programming using the C++ programming language in designing an automatic hand sanitizer system. Furthermore, the research is expected to enhance creativity, innovation, and knowledge development in response to technological advancements. The practical benefits of this research include facilitating students, teachers, and guests at SD Kanisius Genuk in using the automatic hand sanitizer, thus reducing the risk of virus transmission. Additionally, this research can serve as a reference for universities and contribute to the field of human resource management knowledge.